Release film and method for manufacturing multilayer electronic component using the same

By using heterocyclic compounds with nitrogen content and polysiloxane in the release layer of the ceramic green sheet to adjust the atomic ratio of nitrogen and silicon, the static and peeling problems of the ceramic green sheet during detachment are solved, and a lower defect rate and higher product quality are achieved.

JP2025048724APending Publication Date: 2025-04-03SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024093515
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-06-10
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

When manufacturing multi-layer ceramic capacitors (MLCCs), the traditional silicated polymer release layer causes electrostatic problems when the ceramic green sheet is detached from the release film, resulting in peeling defects during disengagement, affecting yield and product short-circuit rate.

Method used

Using a release layer containing a heterocyclic compound with nitrogen content and polysiloxane, the atomic ratio of nitrogen to silicon is determined by photoelectric spectroscopy to improve the detachment performance of the ceramic green sheet.

Benefits of technology

It effectively reduces the peeling force and electrostatic force of the ceramic green sheet when it is detached, reduces the defect rate, and improves the production and quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048724000001_ABST
    Figure 2025048724000001_ABST
Patent Text Reader

Abstract

To provide a release film that generates low peeling force and low static electricity during peeling, and can produce ceramic green sheets with fewer defects; and a method for manufacturing a multilayer electronic component using the same.SOLUTION: There is provided a release film including: a base film; and a release layer disposed on one surface of the base film, wherein the release layer is a cured layer of a release composition including a heterocyclic compound including nitrogen and polydimethylsiloxane, and when analyzing a surface using X-ray photoelectron spectroscopy (XPS), the release layer has an atomic ratio (N / Si) of nitrogen (N) to silicon (Si) of 0.6 to 1.1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film and a method for producing a multilayer electronic component using the same. [Background technology]

[0002] Generally, release films having a polyester film as a base material and a release layer laminated thereon are used for forming ceramic green sheets used in manufacturing multilayer electronic components, such as multilayer ceramic capacitors (hereinafter referred to as "MLCC").

[0003] Meanwhile, after a ceramic green sheet is formed by applying a ceramic slurry onto a release film for manufacturing MLCCs and drying the ceramic slurry, problems such as peeling failure may occur due to static electricity generated when the ceramic green sheet is separated from the release film, which causes defects and short circuits in the finished MLCCs, resulting in a decrease in yield.

[0004] In order to solve these problems, there is a need for research into release films having release layers mainly composed of non-silicon components, rather than the conventional release layers mainly composed of polymeric silicone. Summary of the Invention [Problem to be solved by the invention]

[0005] One of several objects of the present invention is to provide a release film which generates low peeling force and low static electricity during peeling and which enables the formation of ceramic green sheets with fewer defects.

[0006] However, the scope of the present invention is not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]

[0007] One embodiment of the present invention provides a release film comprising a base film and a release layer disposed on one surface of the base film, the release layer being a cured layer of a release composition comprising a nitrogen-containing heterocyclic compound and polydimethylsiloxane, the release layer having an atomic ratio (N / Si) of nitrogen (N) to silicon (Si) of 0.6 to 1.1 upon surface analysis using X-ray photoelectron spectroscopy (XPS). Effect of the Invention

[0008] One of the various effects of the present invention is that it is possible to provide a release film which generates low peeling force and low static electricity during peeling and which can form ceramic green sheets with fewer defects. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view illustrating a release film according to one embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view illustrating a state in which a ceramic green sheet is formed on the release film of FIG. 1. [Diagram 3] 1 is a cross-sectional view illustrating a multilayer electronic component manufactured using a release film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be exaggerated for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0011] In the drawings, parts that are not relevant to the description are omitted in order to clearly explain the present invention, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited to those shown in the drawings. In addition, components that have the same function within the same concept are described using the same reference numerals. Furthermore, throughout the specification, when a part is said to "include" a certain component, this does not exclude other components, but means that the part may further include other components, unless otherwise specified.

[0012] Furthermore, throughout the specification, the terms "~-based compound", "~-based resin", "~-based polymer", "~-based polymer", and "~-based copolymer" are broad concepts including "~-compound", "~-resin", "~-polymer", "~-polymer", "~-copolymer", and / or derivatives thereof.

[0013] In the drawings, the first direction can be defined as a thickness T direction, the second direction can be defined as a length L direction, and the third direction can be defined as a width W direction.

[0014] Release Film FIG. 1 is a cross-sectional view illustrating a release film in accordance with one embodiment of the present invention, and FIG. 2 is a cross-sectional view illustrating a state in which a ceramic green sheet is formed on the release film of FIG.

[0015] A release film 100 according to one embodiment of the present invention includes a base film 110 and a release layer 120 disposed on the base film 110. The release layer 120 is a cured layer of a release composition containing a nitrogen-containing heterocyclic compound and polydimethylsiloxane. The release layer 120 may have an atomic ratio (N / Si) of nitrogen (N) to silicon (Si) of 0.6 to 1.1 upon surface analysis using X-ray photoelectron spectroscopy (XPS).

[0016] 1. Base film The base film 110 constituting the release film 100 of one embodiment of the present invention can be a known film that is widely used in the conventional release film field, and the type of base film 110 is not particularly limited.

[0017] The base film 110 may include a polyester-based compound or a polyester-based polymer, and may have at least one main repeat unit selected from ethylene terephthalate and ethylene naphthalate. As an example, the base film 110 may include polyethylene terephthalate (PET) formed by condensation polymerization of ethylene glycol and terephthalic acid. In this case, the polyethylene terephthalate may be manufactured using the above-mentioned direct method using terephthalic acid, but is not limited thereto.

[0018] In addition, taking into consideration heat resistance, chemical resistance, mechanical strength, and economic efficiency, it is preferable to use polyethylene terephthalate as the base film 110, and more specifically, it is preferable to use a uniaxially or biaxially stretched polyethylene terephthalate film.

[0019] In addition, in order to improve the slipperiness of the release film 100, the base film 110 may contain one or more particles of silica, silicon oxide, calcium carbonate, calcium sulfate, calcium phosphate, magnesium carbonate, magnesium phosphate, barium carbonate, kaolin, aluminum oxide, and titanium oxide, but the present invention is not limited thereto.

[0020] The thickness ts of the base film 110 may be, for example, 10 μm to 200 μm, but the present invention is not limited to this.

[0021] 2.Release layer The release layer 120 according to an embodiment of the present invention may be disposed on one surface of the substrate film 110. The release layer 120 may be a cured layer of a release composition including a nitrogen-containing heterocyclic compound and polydimethylsiloxane.

[0022] (Heterocyclic compounds) The heterocyclic compound contained in the release composition may be the main component of the release layer 120. The heterocyclic compound can provide the release layer with a high elastic modulus, thereby facilitating the winding process of the release film (the process of winding the release film into a roll). In addition, the heterocyclic compound can provide the release composition with high surface energy, thereby improving the applicability of the release composition to the substrate film.

[0023] The heterocyclic compound contained in the mold release composition may contain nitrogen, and the nitrogen-containing heterocyclic compound may include one or more of melamine, ammeline, melam, and melem. In one embodiment, the nitrogen-containing heterocyclic compound may include one or more of ammeline, melam, and melem.

[0024] The heterocyclic compound may include, for example, one or more of methoxymethylmelamine, ethoxymethylmelamine, propoxymethylmelamine, butoxymethylmelamine, hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexabutoxymethylmelamine, hexapentyloxymethylmelamine, and hexahexyloxymethylmelamine, but the invention is not limited thereto.

[0025] The heterocyclic compound may include, for example, one or more of the compounds represented by the following chemical formulas 1 to 4. In one embodiment, the heterocyclic compound may include one or more of the compounds represented by the following chemical formulas 2 to 4.

[0026] [ka] (Here, X represents a hydrogen atom, -CHOH, or -CH-OR, and each may be the same or different. R represents an alkyl group having 1 to 8 carbon atoms, and each may be the same or different.)

[0027] [ka]

[0028] [ka]

[0029] [ka]

[0030] (Polydimethylsiloxane) The polydimethylsiloxane contained in the release composition is an additive for imparting releasability to the release layer, and by combining with the melamine-based compound of the release composition, the durability of the release layer can be improved.

[0031] On the other hand, it is more preferable that the polydimethylsiloxane contained in the mold release composition has a functional group. The functional group may be introduced at one or both ends of the polydimethylsiloxane, and the position at which the functional group is introduced may be one or more.

[0032] The polydimethylsiloxane may have, as a functional group, a cyclic ether group, a hydroxy group, a mercapto group, a carboxyl group, a methacryloyl group, an acryloyl group, a polyether group, an alkyl group, a fluoroalkyl group, a long-chain alkyl group, an ester group, an amide group, a phenyl group, a vinyl group, and / or a hexenyl group, and preferably has hydroxyl groups at both ends for bonding with a heterocyclic compound, although the present invention is not limited thereto.

[0033] The content of polydimethylsiloxane contained in the mold release composition is not particularly limited, but may be 3 parts by weight or more and 25 parts by weight or less based on 100 parts by weight in total of the heterocyclic compound and the polydimethylsiloxane.

[0034] The weight average molecular weight of the polydimethylsiloxane contained in the release composition does not need to be particularly limited, but may be from 1000 to 500,000. If the weight average molecular weight of the polydimethylsiloxane is less than 1000, the releasability of the release film may decrease, and if the weight average molecular weight of the polydimethylsiloxane is more than 500,000, the viscosity of the release composition may become too high, resulting in a decrease in the flatness of the release layer.

[0035] (acid catalyst) In one embodiment, the release composition may further include an acid catalyst in addition to the above components. The acid catalyst may play a role in promoting a crosslinking reaction with the heterocyclic compound contained in the release composition.

[0036] The acid catalyst may include, for example, one or more of methanesulfonic acid, trifluoromethanesulfonic acid, isoprene sulfonic acid, camphorsulfonic acid, hexanesulfonic acid, octane sulfonic acid, nonanesulfonic acid, decane sulfonic acid, hexadecanesulfonic acid, dinonylnaphthalenesulfonic acid, dinonylnaphthalenedisulfonic acid, benzenesulfonic acid, alkylbenzenesulfonic acid, paratoluenesulfonic acid, melamine trisulfonic acid (MTSA), cumenesulfonic acid, dodecylbenzenesulfonic acid, naphthalenesulfonic acid, and nonylnaphthalenesulfonic acid. From the viewpoint of reactivity with the heterocyclic compound, it is preferable that the release composition includes paratoluenesulfonic acid.

[0037] The amount of the acid catalyst added is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the heterocyclic compound. If the content of the acid catalyst is less than 0.1 parts by weight relative to 100 parts by weight of the heterocyclic compound, the curing reaction may be slow, and if the content of the acid catalyst is more than 10 parts by weight relative to 100 parts by weight of the heterocyclic compound, the storage stability of the mold release composition may be reduced.

[0038] (Solvents and other components) In one embodiment, the release composition may further include a binder, a conductivity enhancer, a pH adjuster, a surfactant, etc., within the range that does not change the properties of the release layer, and may include a remaining amount of a solvent.

[0039] The above-mentioned solvent may be any solvent that is compatible with the heterocyclic compound. For example, one or more of acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, xylene, methanol, ethanol, butanol, isopropyl alcohol, isobutyl alcohol, ethyl acetate, butyl acetate, propyl acetate, isopropyl acetate, hexane, heptane, octane, and isooctane may be used as the above-mentioned solvent.

[0040] (Characteristics of the release layer) According to one embodiment of the present invention, the release layer 120 may have an atomic ratio (N / Si) of nitrogen (N) to silicon (Si) of 0.6 to 1.1 when surface analysis is performed using X-ray photoelectron spectroscopy (XPS). If the atomic ratio (N / Si) of nitrogen to silicon is outside the above range, the release property of the release film 100 may be reduced, and a problem may occur in that the ceramic green sheet cannot be smoothly peeled off, which may cause wrinkles or burns on the sheet.

[0041] Specifically, when the atomic ratio of nitrogen to silicon (N / Si) is less than 0.6, the release composition is less applicative and moldable, and the sheet may suffer from wrinkles, burns, etc. When the atomic ratio of nitrogen to silicon (N / Si) is more than 1.1, the peeling force required to peel the ceramic green sheet from the release film increases, and the sheet may suffer from wrinkles, burns, etc.

[0042] Nitrogen (N) detected during XPS analysis of the surface of the release layer 120 may be derived from a heterocyclic compound containing nitrogen, and silicon (Si) detected during XPS analysis may be derived from polydimethylsiloxane. The atomic ratio of nitrogen to silicon (N / Si) may be adjusted, for example, depending on the content and type of the heterocyclic compound and polydimethylsiloxane, but the present invention is not limited thereto.

[0043] In one embodiment, the content of nitrogen (N) element among all elements contained in the release layer 120 may be 11.0 wt% or more and 21.1 wt% or less. The content of nitrogen (N) element contained in the release layer 120 may be determined according to the content of the heterocyclic compound contained in the release composition. If the content of nitrogen (N) element contained in the release layer 120 is outside the above range, the release property of the release film 100 may be reduced, and wrinkles or burns of the sheet may occur.

[0044] In one embodiment, the maximum height roughness Rmax of the release layer 120 may be 70 nm or less. When the maximum height roughness Rmax of the release layer 120 is 70 nm or less, the release layer 120 can exhibit high smoothness. This makes it possible to suppress the occurrence of defects such as pinholes when forming the ceramic green sheet GS on the release layer 120.

[0045] In this specification, the maximum height roughness Rmax of the release layer 120 can be measured based on the ISO 25178 (Geometric Product Specifications (GPS)-Surface texture:areal) standard. The maximum height roughness Rmax of the release layer 120 can be measured, for example, using a three-dimensional contact surface roughness measuring device. More specifically, the maximum height roughness Rmax of the release layer 120 can be calculated by taking a reference length from a cross-sectional curve via a surface roughness measuring device, and calculating the distance between two parallel lines that are parallel to the center of the cross-sectional curve and are in contact with the highest peak and the deepest valley.

[0046] The lower limit of the maximum height roughness Rmax of the release layer 120 does not need to be particularly limited, and may be greater than 0 nm.

[0047] In one embodiment, the ratio tr / ts of the thickness tr of the release layer 120 to the thickness ts of the base film 110 may be 0.005 or more and 0.027 or less. If the value of tr / ts is less than 0.005, the surface roughness characteristics of the release layer 120 may be degraded. Also, if the value of tr / ts is more than 0.027, the peeling force generated when peeling the ceramic green sheet GS from the release film 100 may be excessively increased.

[0048] Here, the thickness tr of the release layer 120 means the thickness after the release composition has been dried and cured. The thickness ts of the base film 110 and the thickness tr of the release layer 120 can be measured by observing the cross section of the release film 100 with a scanning electron microscope (SEM).

[0049] In one embodiment, the surface energy of the release layer 120 may be 28 mN / m or more and 30 mN / m or less. The surface energy of the release layer 120 is related to the coatability and peeling force of the release layer 120. Specifically, the higher the surface energy of the release layer 120, the better the coatability of the ceramic slurry applied onto the release layer 120, and the lower the surface energy of the release layer 120, the better the peelability of the release film 100.

[0050] That is, if the surface energy of the release layer 120 is less than 28 mN / m, there is a possibility that the wettability and smoothness may decrease when applying a ceramic slurry onto the release layer 120. Also, if the surface energy of the release layer 120 exceeds 30 mN / m, there is a possibility that the peeling force of the release film 100 may become excessively high.

[0051] 3.Antistatic layer In one embodiment, an antistatic layer 130 may be further disposed on the other side of the substrate film 110 opposite to the side on which the release layer 120 is disposed. The antistatic composition forming the antistatic layer 130 may include antistatic particles and a binder.

[0052] The antistatic particles contained in the antistatic composition may be, for example, a conductive polymer resin, and may include, but is not limited to, polythiophene, polypyrrole, polyaniline, polyethylenedioxythiophene (PEDOT), or mixtures thereof.

[0053] The binder contained in the antistatic composition may be, for example, a polyester-based binder, but the present invention is not limited thereto.

[0054] Manufacturing method for multilayer electronic components FIG. 3 is a cross-sectional view that illustrates a multilayer electronic component 200 manufactured using a release film according to one embodiment of the present invention.

[0055] The multilayer electronic component 200 may include a body 210 including a dielectric layer 211 and internal electrodes 221, 222, and external electrodes 231, 232 disposed outside the body 210 and connected to the internal electrodes 221, 222. More specifically, the multilayer electronic component 200 may include a first external electrode 231 connected to the first internal electrode 221 and a second external electrode 232 connected to the second internal electrode 222.

[0056] Further, the main body 210 may include a capacitance forming portion in which a capacitance is formed including a first internal electrode 221 and a second internal electrode 222 that are alternately arranged with a dielectric layer 211 interposed therebetween, and cover portions 212 and 213 that are arranged on both surfaces facing the first direction of the capacitance forming portion.

[0057] Hereinafter, an example of a method for manufacturing a laminated electronic component 200 using the release film 100 according to an embodiment of the present invention will be described. The release film 100 according to the embodiment of the present invention described above can be used as a carrier film for forming a ceramic green sheet.

[0058] First, ceramic powder for forming the dielectric layer 211 is prepared. The ceramic powder is not particularly limited as long as sufficient capacitance can be obtained. For example, barium titanate-based materials, lead composite perovskite-based materials, or strontium titanate-based materials can be used. As examples of the ceramic powder, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium), Zr (zirconium), etc. are partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc. can be mentioned. Among the above ceramic powders, BaTiO3 can be synthesized, for example, by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. Examples of the synthesis method of the ceramic powder include, for example, a solid-phase method, a sol-gel method, a hydrothermal synthesis method, etc., but the present invention is not limited thereto.

[0059] Next, a ceramic powder, an organic solvent such as ethanol, and a binder such as polyvinyl butyral can be mixed to prepare a ceramic slurry. Then, the ceramic slurry is applied to a release film 100 according to one embodiment of the present invention and dried to form a ceramic green sheet GS. The average thickness tg of the ceramic green sheet GS does not need to be particularly limited, but may be, for example, 0.5 μm to 5.0 μm.

[0060] In one embodiment, the maximum height roughness Rmax of the ceramic green sheet GS may be 53 nm or less. By forming a ceramic green sheet using the release film 100 according to one embodiment of the present invention, the maximum height roughness Rmax of the ceramic green sheet can satisfy the above range. This can prevent wrinkles and burns of the sheet.

[0061] Next, an internal electrode pattern can be formed on the ceramic green sheet GS. The internal electrode pattern can be formed by firing to form internal electrodes 221, 222. The internal electrode pattern can be formed by printing a conductive paste for internal electrodes containing metal powder, binder, etc., on the ceramic green sheet GS to a predetermined thickness using a screen printing method, a gravure printing method, etc. The metal powder can include, for example, one or more of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, but the present invention is not limited thereto.

[0062] Next, a predetermined number of ceramic green sheets GS on which the internal electrode patterns are formed can be stacked and pressed to form a ceramic laminate. Also, in order to form cover parts 212, 213 after firing, a predetermined number of ceramic green sheets GS on which no internal electrode patterns are printed can be stacked on the upper and lower parts in the first direction of the ceramic laminate. Meanwhile, it is preferable to peel off the ceramic green sheets GS from the release film 100 before stacking the ceramic green sheets GS.

[0063] In one embodiment, the peeling force when peeling the ceramic green sheet GS from the release film 100 at a peeling angle of 90° may be 35 mN / 40 mm or less. More specifically, the peeling force when peeling the ceramic green sheet GS from the release film 100 at a peeling speed of 300 mm / min and a peeling angle of 90° may be 35 mN / 40 mm or less. This can prevent defects such as pinholes or wrinkles from occurring in the ceramic green sheet GS when peeling the ceramic green sheet GS from the release film 100. The lower limit of the peeling force when peeling the ceramic green sheet GS from the release film 100 at a peeling angle of 90° does not need to be particularly limited, but may be 10 mN / 40 mm or more, 20 mN / 40 mm or more, or 25 mN / 40 mm or more to achieve an intended light or heavy peeling force.

[0064] In one embodiment, the difference between the work function (eV) of the ceramic green sheet GS measured using ultraviolet photoelectron spectroscopy (UPS) and the work function (eV) of the release layer 120 may be ±0.7 eV or less. When the difference in work function between the ceramic green sheet GS and the release layer 120 satisfies the above range, the amount of static electricity generated due to the difference in the charging order may be reduced, resulting in a reduction in the peel force.

[0065] The ceramic laminate may be cut into chips of a predetermined size as necessary, but the present invention is not limited thereto. In addition, it is preferable to remove binders and the like contained in the ceramic laminate or the cut chips by a binder removal process. The conditions of the binder removal process vary depending on the type of binder used, and are not particularly limited.

[0066] Thereafter, the ceramic laminate can be fired. Alternatively, the cut chips can be fired. The firing temperature is not particularly limited, but may be, for example, 1100° C. or higher and 1300° C. or lower. The ceramic laminate or the cut chips can be fired to form the main body 210 including the dielectric layer 211 and the internal electrodes 221, 222.

[0067] Finally, the external electrodes 231, 232 can be formed. First, the body 210 is dipped in a conductive paste containing metal powder and glass, and then fired to form the electrode layers 231a, 232a. In this case, the firing temperature may be, for example, 700°C to 900°C.

[0068] Next, the plating layers 231b, 232b can be formed using an electrolytic plating method and / or an electroless plating method. The plating layers 231b, 232b can improve mounting characteristics, and may be plating layers containing Ni, Sn, Pd and / or alloys containing these, or may be formed of a plurality of layers. For example, the plating layers 231b, 232b may be in a form in which a Ni plating layer and a Sn plating layer are formed in sequence.

[0069] However, the above-mentioned manufacturing method is just one example, and the method for manufacturing the multilayer electronic component 200 is not limited to the above-mentioned manufacturing method.

[0070] Hereinafter, the configuration and effects of the present invention will be described in more detail with reference to examples and comparative examples. However, it is obvious that the following examples are provided to more specifically explain the present invention, and the scope of the present invention is not limited to the following experimental examples.

[0071] Example 1 Melamine and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of the total elements of the release layer was 11 wt%, and then added to a solvent, isopropyl alcohol (IPA). Next, 0.5 wt% of paratoluenesulfonic acid was added to the solvent as an acid catalyst to prepare a release composition.

[0072] The release composition was applied onto one side of a polyester substrate film, and the resulting film was subjected to a curing heat treatment for 1 minute in a hot air dryer at 120° C. to form a release layer, thereby producing a release film. In addition, the amount of the release composition applied was adjusted so that the ratio of the thickness of the release layer to the thickness of the substrate film after drying and curing was 0.013.

[0073] Example 2 A release film was prepared in the same manner as in Example 1, except that melamine and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 21.1 wt% and then added to the solvent.

[0074] Example 3 A release film was prepared in the same manner as in Example 1, except that ammeline and polydimethylsiloxane were stoichiometrically weighed and then added to the solvent so that the nitrogen (N) content of all elements in the release layer was 20.8 wt%.

[0075] Example 4 A release film was prepared in the same manner as in Example 1, except that melam and polydimethylsiloxane were stoichiometrically weighed and then added to the solvent so that the nitrogen (N) content of the total elements in the release layer was 19.6 wt%.

[0076] Example 5 A release film was prepared in the same manner as in Example 1, except that melem and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 20.9 wt% and then added to the solvent.

[0077] Example 6 A release film was prepared in the same manner as in Example 1, except that melamine and polydimethylsiloxane were stoichiometrically weighed and then added to the solvent so that the nitrogen (N) element content of all elements in the release layer was 20.9 wt%, and the ratio of the thickness of the release layer to the thickness of the base film after drying and curing was adjusted to 0.005.

[0078] Example 7 A release film was prepared in the same manner as in Example 6, except that after drying and curing, the ratio of the thickness of the release layer to the thickness of the base film was adjusted to be 0.013.

[0079] Example 8 A release film was prepared in the same manner as in Example 6, except that after drying and curing, the ratio of the thickness of the release layer to the thickness of the base film was adjusted to 0.027.

[0080] Comparative Example 1 Only polydimethylsiloxane was added to the solvent. Next, 0.5 wt% of platinum (Pt) catalyst was added to the solvent to prepare a release composition. Except for the above differences, a release film was prepared in the same manner as in Example 1.

[0081] Comparative Example 2 A release film was prepared in the same manner as in Example 1, except that melamine and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 10.1 wt% and then added to the solvent.

[0082] Comparative Example 3 A release film was prepared in the same manner as in Example 1, except that melamine and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 21.6 wt% and then added to the solvent.

[0083] Comparative Example 4 A release film was prepared in the same manner as in Example 1, except that ammeline and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 9.9 wt% and then added to the solvent.

[0084] Comparative Example 5 A release film was prepared in the same manner as in Example 1, except that melam and polydimethylsiloxane were stoichiometrically weighed and then added to the solvent so that the nitrogen (N) content of the total elements in the release layer was 26.2 wt%.

[0085] Comparative Example 6 A release film was prepared in the same manner as in Example 1, except that melem and polydimethylsiloxane were stoichiometrically weighed so that the nitrogen (N) content of all elements in the release layer was 29.0 wt% and then added to the solvent.

[0086] Comparative Example 7 A release film was prepared in the same manner as in Example 1, except that melamine and polydimethylsiloxane were stoichiometrically weighed and then added to the solvent so that the nitrogen (N) content of all elements in the release layer was 20.9 wt%, and the ratio of the thickness of the release layer to the thickness of the substrate film after drying and curing was adjusted to 0.003.

[0087] Comparative Example 8 A release film was prepared in the same manner as in Comparative Example 7, except that after drying and curing, the ratio of the thickness of the release layer to the thickness of the base film was adjusted to 0.031.

[0088] (Evaluation of physical properties) 1.XPS analysis The surface of the release layer of the release film was subjected to component analysis using X-ray photoelectron spectroscopy (XPS). After measuring the silicon element content (at%) and nitrogen element content (at%) detected by the XPS analysis, the atomic ratio of nitrogen to silicon (N / Si) was shown in Table 1 below.

[0089] 2. Measurement of maximum height roughness Rmax The maximum height roughness Rmax of the release films produced in the examples and comparative examples was measured using a contact type three-dimensional surface roughness measuring device (Bruker, ContourX-500 product) based on the ISO 25178 (Geometric Product Specifications (GPS)-Surface texture:areal) standard, and the results are shown in Table 1 below.

[0090] In addition, the ceramic slurry was coated on the release layer of the release film of each of the examples and comparative examples, and then dried to form a ceramic green sheet, and the maximum height roughness Rmax of the ceramic green sheet was measured in the same manner.

[0091] 3. Surface Energy Measurement Distilled water and diiodomethane were dropped onto the release layer of the release films prepared in the examples and comparative examples, and the contact angle of the droplet formed on the release layer was measured using a contact angle meter (Phoenix300Touch product). The measured contact angle value was substituted into the Owens-Wendt model to calculate the surface energy, which is shown in Table 1 below.

[0092] 4. Work Function Measurement The work function difference between the release layer of the release film prepared in the examples and comparative examples and the ceramic green sheet was measured by ultraviolet photoelectron spectroscopy (UPS).

[0093] First, the release compositions prepared in the Examples and Comparative Examples were spin-coated on a conductive glass substrate having a glass layer and an ITO layer stacked in sequence to prepare samples for measuring the work function. Then, the work function of the release layer was measured by UPS analysis.

[0094] Next, the ceramic slurry was spin-coated on the conductive glass substrate to prepare a sample for work function measurement, and the work function of the ceramic green sheet was then measured by UPS analysis.

[0095] Finally, the absolute value of the difference between the work function of the release layer formed with the release composition prepared in each of the Examples and Comparative Examples and the work function of the ceramic green sheet was calculated and is shown in Table 1 below.

[0096] 4. Peel Force Measurement The ceramic slurry was coated on the release layer of the release film of each of the Examples and Comparative Examples and dried to form a ceramic green sheet. The ceramic green sheet, 40 mm wide and 100 mm long, was peeled from the release film at a peel speed of 300 mm / min and a peel angle of 90°. The peel force was measured using a peel force measuring device and is listed in Table 1 below.

[0097] 5. Electrostatic Force Measurement The ceramic slurry was coated on the release layer of the release film of each of the Examples and Comparative Examples, and then dried to form a ceramic green sheet. The amount of static electricity was then measured using a static electricity meter when peeling the ceramic green sheet from the release film, and the results are shown in Table 1 below.

[0098] 6. Measurement of sheet wrinkle defect rate and burnt frequency The ceramic slurry was applied to the release film of each of the examples and comparative examples, and then dried to form a ceramic green sheet, which was then peeled off from the release film. The ratio of the ceramic green sheets that remained folded or wrinkled inside the sample chip, which was made by laminating a plurality of the ceramic green sheets, was measured and shown in Table 1 below.

[0099] In addition, when 20 layers of each of the ceramic green sheets manufactured using the release films of the Examples and Comparative Examples were laminated, the number of times that burnt marks occurred due to the generated static electricity is shown in Table 1 below.

[0100] [Table 1]

[0101] Referring to Table 1 above, it can be seen that the release films manufactured in Examples 1 to 8 have excellent releasability and antistatic properties compared to the release films manufactured in Comparative Examples 1 to 8 because the atomic ratio of nitrogen to silicon (N / Si) is 0.6 or more and 1.1 or less. This confirms that the release films according to the examples have a lower rate of wrinkle defects and a lower number of burns compared to the release films according to the comparative examples. This shows that the release films manufactured in Examples 1 to 8 are suitable for manufacturing processes of laminated electronic components, particularly MLCCs.

[0102] The present invention is not limited by the above-described embodiments and the accompanying drawings, but is limited by the scope of the accompanying claims. Therefore, various substitutions, modifications and changes can be made by a person having ordinary knowledge in the art without departing from the technical idea of ​​the present invention described in the claims, and these also belong to the scope of the present invention.

[0103] In addition, the expression "one embodiment" does not mean the same embodiment, but is provided to emphasize and describe each unique feature that is different from the others. However, the above-mentioned one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description that is opposite or contradictory to the matter in the other embodiment. [Explanation of symbols]

[0104] 100: Release film 110: Base film 120: Release layer 130: Antistatic layer 200: Multilayer electronic components 210: Main unit 211: Dielectric layer 212, 213: Cover part 221, 222: Internal electrode 231, 232: External electrode

Claims

1. A base film; A release layer disposed on one surface of the base film, the release layer is a cured layer of a release composition containing a nitrogen-containing heterocyclic compound and polydimethylsiloxane; The release layer has an atomic ratio (N / Si) of nitrogen (N) to silicon (Si) of 0.6 to 1.1 when surface analysis is performed using X-ray photoelectron spectroscopy (XPS).

2. 2. The release film according to claim 1, wherein the release layer has a maximum height roughness Rmax of 70 nm or less.

3. 2. The release film according to claim 1, wherein a ratio of a thickness of the release layer to a thickness of the base film is 0.005 or more and 0.027 or less.

4. The release film according to claim 1 , wherein the surface energy of the release layer is 28 mN / m or more and 30 mN / m or less.

5. 2. The release film according to claim 1, wherein the heterocyclic compound comprises one or more of melamine, ammeleine, melam, and melem.

6. 2. The release film according to claim 1, wherein the heterocyclic compound comprises one or more of ammeleine, melam, and melem.

7. The release film of claim 1 , wherein the release composition further comprises paratoluene sulfonic acid.

8. The release film according to claim 1 , further comprising an antistatic layer disposed on the other surface opposite to the one surface of the base film.

9. A step of forming a ceramic green sheet by applying a ceramic slurry onto the release film according to any one of claims 1 to 8; forming an internal electrode pattern on the ceramic green sheet; forming a ceramic laminate by stacking the ceramic green sheets on which the internal electrode patterns are formed; and firing the ceramic laminate.

10. peeling the ceramic green sheets from the release film before laminating the ceramic green sheets; 10. The method for producing a multilayer electronic component according to claim 9, wherein a peel force when peeling the ceramic green sheet from the release film at a peel speed of 300 mm / min and a peel angle of 90° is 35 mN / 40 mm or less.

11. 10. The method for producing a multilayer electronic component according to claim 9, wherein a difference between a work function (eV) of the ceramic green sheet and a work function (eV) of the release layer measured using ultraviolet photoelectron spectroscopy (UPS) is ±0.7 eV or less.

12. 10. The method for producing a multilayer electronic component according to claim 9, wherein the ceramic green sheets have an average thickness of 0.5 μm to 5.0 μm.